Rethinking Intentionality, Person and the Essence
1 online resource (254 pages)
Keywords: What is the relationship between the concept of person and the concept of intentionality? Is the phenomenological notion of essence somehow related to that of medieval philosophies? What kind of entity is the person understood in her irreducible singularity? These are some of the questions that the chapters in this book seek to address and develop by focusing on the thought of Aquinas, Scotus and Edith Stein. Indeed, the editors of the book are led by the conviction that a fruitful dialogue between medieval philosophy and 20th century phenomenology may prove useful in addressing questions and problems that are still relevant in contemporary debates. The book is divided into three sections, devoted respectively to medieval philosophy, phenomenology and some of the possible systematic and historical intersections between them. Contributors are Sarah Borden Sharkey, Antonio Calcagno, Therese Cory, Daniele De Santis, Andrew LaZella, Dominik Perler, Giorgio Pini, Francesco Valerio Tommasi, Anna Tropia, and Ingrid Vendrell Ferran.